2021
DOI: 10.48550/arxiv.2110.15806
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simulating quantum repeater strategies for multiple satellites

Julius Wallnöfer,
Frederik Hahn,
Mustafa Gündoğan
et al.

Abstract: A global quantum repeater network involving satellite-based links is likely to have advantages over fiberbased networks in terms of long-distance communication, since the photon losses in free space scale only polynomially with the distance -compared to the exponential losses in optical fibers. To simulate the performance of such networks, we have introduced a scheme of large-scale event-based Monte Carlo simulation of quantum repeaters with multiple memories that can faithfully represent loss and imperfection… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Hence, it can be concluded that employing quantum memories at memory-assisted ground nodes in conjunction with multiple satellites is a next step to increase the range of entanglement distribution even further. Finally, intermediary nodes may be moved onto satellites, improving fidelity by avoiding unnecessary light paths through the atmosphere altogether [28,29]. Building space-based quantum networks in this manner not only aids the establishment of future global quantum communication, but may also be utilized in fundamental science studies in space.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it can be concluded that employing quantum memories at memory-assisted ground nodes in conjunction with multiple satellites is a next step to increase the range of entanglement distribution even further. Finally, intermediary nodes may be moved onto satellites, improving fidelity by avoiding unnecessary light paths through the atmosphere altogether [28,29]. Building space-based quantum networks in this manner not only aids the establishment of future global quantum communication, but may also be utilized in fundamental science studies in space.…”
Section: Introductionmentioning
confidence: 99%
“…In such a network, entanglement could be distributed over continental distances (up to a few thousand km) using ground fiber-based quantum repeaters [5,19], while longer distances could be reached using satellites, e.g. by performing entanglement swapping between quantum memories placed in LEO satellites [1,2,20], or by entangling quantum memories located in separate ground stations with entangled photon sources located on LEO satellites [16]. As is well established, optical fibers are commonly used to establish metropolitan quantum networks [21,22].…”
Section: A Ultra-long Distance Entanglement and Teleportation Experim...mentioning
confidence: 99%
“…The emergence of terrestrial quantum networks in large metropolitan areas demonstrates an increasing maturity of quantum technologies. A networked infrastructure enables increased capabilities for distributed applications in delegated quantum computing [1,2], quantum communications [3,4], and quantum sensing [5]. However, extending these applications over global scales is currently not possible owing to exponential losses in optical fibres.…”
Section: Introductionmentioning
confidence: 99%